New Chondrichthyans from the Upper Cretaceous (Campanian–Maastrichtian) of Seymour and James Ross Islands, Antarctica. (May 2014) - Otero, Rodrigo A.; Gutstein, Carolina Simon; Vargas, Alexander; Rubilar-Rogers, David; Yury-Yañez, Roberto; Bastías, Joaquin; Ramírez, Cristián
Abstract : We present new records of chondrichthyans recovered from strata of Maastrichtian age of the López de Bertodano Formation, Seymour (=Marambio) Island, and from levels of latest Campanian age of the Santa Marta Formation, James Ross Island, both located in the eastern Antarctic Peninsula. The material from Marambio Island comprises an associated assemblage with the first records of an indeterminate odontaspidid different from Odontaspis, as well as the genera Pristiophorus, Squatina, Paraorthacodus, and the species Chlamydoselachus tatere from the López de Bertodano Formation. Also, the studied section provides a well-constrained age for several taxa already recognized in the López de Bertodano Formation only by scattered samples of Maastrichtian age for the first time. The assemblage from Marambio Island is representative of one of the latest environmental conditions during the end of the Cretaceous in the coastal seas of the Larsen Basin before major changes that began after the K/P boundary. In addition, the finds from James Ross Island comprise the southernmost records of the neoselachians Cretalamna sp., Centrophoroides sp., as well as the holocephalans Callorhinchus sp. and an indeterminate rhinochimaerid, extending the occurrence of some of these taxa into the late Campanian, being their oldest record of the Weddellian Biogeographic Province.